A research on customer satisfaction towards Hotel Ansar services / Masliza Mohd Nasir - Mohd Nasir, Masliza (2000)
Lodging continually changes to accommodate its guests. These changes may also involve customer satisfaction, which is an important ingredient in the marketer's formula for success This research is developed to identify the degree of customer satisfaction towards Hotel Ansar service and element affecting it. This research was carried out in the Hotel Ansar premise, which involved 98 respondents selected among the In-house guests of the hotel. The researcher managed to use systematic sampling in distributing the questionnaires. The data gathered was then produced into meaningful information using the Statistical Package for Social Sciences (SPSS) computer program. "The data afterwards gone through the stage of analyzing and interpreting. The findings of this research show that the level of customer satisfaction towards the services of Hotel Ansar is moderate. There were respondents who satisfied with the services provided, and there were some others who did not agree with the services. Thus, Hotel Ansar should find ways to overcome the weaknesses and problems exist in the operation and management of the hotel to make sure the services delivered able to fulfil the expectations of its guests.